The HGF receptor, a targettable regulator of invasive growth - Comoglio, Paolo (Henry Stewart Talks, 2007)
Trigger of invasive growth by specific signals, Invasive growth receptors, The "receptosome", Dynamics of invasive growth signalling, The MET transcriptome, HGF regulated genes, Hypoxia regulates MET transcription, The effector machinery of invasive growth: the coagulation cascade, HGF antagonists impair tumor growth and metastasis: a gene therapy strategy
Archived at 2018/10/28